An insight into the conformal flexibility and vibrational behavior of 2-nitroso-1-naphthol: A density functional theory approach. Issue 4 (20th April 2016) - Ragavendran, V.; Muthunatesan, S.
ABSTRACT: The conformational stability of 2-nitrosol-1-naphthol (2N1N) was elucidated using potential energy surface scan studies. In order to carry out a detailed vibrational spectroscopic analysis of 2N1N, Fourier transform infrared and Fourier transform Raman spectra have been recorded in condensed phase. To determine the optimized geometry and vibrational wavenumber, density functional theory calculations in the B3LYP/6-31G** level have been carried out followed by scaling using the scaled quantum mechanical methodology. A root mean square deviation of 9.69 cm −1 has resulted from the scaled quantum mechanical treatment. Substitution of nitroso group into the 1-naphthol has produced remarkable changes in the structural parameters. The ultraviolet-visible spectra of the title compound dissolved in various solvents were recorded in the range of 300–500 nm. The natural bond orbital analysis, frontier molecular orbital analysis, and thermodynamic features were also performed using B3LYP/6-31G** method.